Interdisciplinarity and interprofessionality in teamwork: perceptions of multiprofessional residents in Hospital Care - Ana Paula de Sousa Silva Baquião; Leonardo Melo Guedes; Claudia Helena Cerqueira Mármora; Rodrigo Sanches Peres; Fabiane Rossi dos Santos Grincenkov (Acta Scientiarum. Health Sciences, 2021)
Multiprofessional Health Residency Programs were created to further align health training with the needs of the population and, through an emphasis on teamwork, have been contributing to the consolidation of the Brazilian Unified Health System. The present study sought to understand the perceptions of a group of multiprofessional residents in Hospital Care about interdisciplinarity and interprofessionality within the scope of teamwork. This is a qualitative study that had the participation of 29 multiprofessional residents in the ‘Hospital Care’ area of concentration, all female (six psychologists, six social workers, six nurses, six physiotherapists and five nutritionists). Data were collected by means of a semi-structured interview script. The corpus was subjected to thematic content analysis. Most of the participants: (1) reported that their first contact with the notion of interdisciplinarity occurred when they were in college, which led to them assimilating it as a synonym for joint action, and (2) claimed to have no knowledge of the notion of interprofessionality, but valued the horizontalization of relations between health professionals. Additionally, important conditions concerning both interdisciplinarity and interprofessionality were not emphasized by the participants. Further studies on the subject are needed, due to its importance for public health.